Dimensions of Community Religious Tolerance in Bejijong Village, Trowulan District, Mojokerto Regency - Bernadetta Budi Lestari; Pandu Rudy Widyatama (PT. Banjarese Pacific Indonesia, 2024)
Religious tolerance is universally important, especially in Indonesia itself. Remembering the journey from the time of the Majapahit Kingdom to the Renaissance period when tolerance became the real basis of people's lives. Religious tolerance is not only imagined as being together of different things but embodying the unity of different behind diversity to achieve the common goal of equality. That is the step and purpose of researchers in analyzing the conditions and environment of the Bejijong village community. Researchers use descriptive qualitative research with observation methods, interviews, and literature studies. Based on what has been found, religious tolerance in Bejijong village is very good with the showing of community activities and activities that illustrate the value of tolerance, such as interfaith dialogue, cultural festivals, and the appearance of the environment seen from the diversity of buildings with the presence of characteristics that accompany each other from various religions.